1990
DOI: 10.1007/bf02257652
|View full text |Cite
|
Sign up to set email alerts
|

Decreased uptake and binding of11C-nicotine in brain of Alzheimer patients as visualized by positron emission tomography

Abstract: Positron emission tomography of the brain following intravenous injection of (+) (R) and (-) (S) N-[11C-methyl]nicotine showed a marked reduced uptake of both isomers, especially the (R) form, in Alzheimer patients as compared to age-matched controls. The significantly larger difference between the uptake values of the (S)- and (R)-enantiomers of 11C-nicotine in Azheimer brains may be of diagnostic value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
52
0
3

Year Published

1996
1996
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(57 citation statements)
references
References 35 publications
2
52
0
3
Order By: Relevance
“…Typically, 1 g of RNA was incubated with 1 unit of DNase I in a 10 l-reaction at room temperature for 15 min, and the DNase I was subsequently inactivated by addition of 1 l of 25 mM EDTA and incubation at 65°C for 10 min. RT was carried out using 0.8 g of DNA-free total RNA and oligo(dT) [12][13][14][15][16][17][18] primer in a 20-l reaction using the Superscript II TM Preamplification system (Invitrogen). At the end of the RT reaction, reverse transcriptase was deactivated by incubation at 75°C for 10 min, and RNAs were removed by adding 1 unit of RNase H followed by incubation at 37°C for 30 min.…”
Section: Rna Preparation and Reverse Transcription (Rt)-pcr-totalmentioning
confidence: 99%
See 1 more Smart Citation
“…Typically, 1 g of RNA was incubated with 1 unit of DNase I in a 10 l-reaction at room temperature for 15 min, and the DNase I was subsequently inactivated by addition of 1 l of 25 mM EDTA and incubation at 65°C for 10 min. RT was carried out using 0.8 g of DNA-free total RNA and oligo(dT) [12][13][14][15][16][17][18] primer in a 20-l reaction using the Superscript II TM Preamplification system (Invitrogen). At the end of the RT reaction, reverse transcriptase was deactivated by incubation at 75°C for 10 min, and RNAs were removed by adding 1 unit of RNase H followed by incubation at 37°C for 30 min.…”
Section: Rna Preparation and Reverse Transcription (Rt)-pcr-totalmentioning
confidence: 99%
“…First, in the brain of AD patients, there is a marked decrease in the numbers of nAChR radioligand binding sites (12), particularly those that have the highest affinity for nicotine and appear to be the most abundant nAChR subtype in the brain of vertebrates (13)(14)(15)(16). Immunoassays show that these nAChRs contain ␣4 and ␤2 subunits (17,18).…”
mentioning
confidence: 99%
“…Nicotinic acetylcholine receptors have been implicated in the treatment or pathophysiology of several neuropsychiatric disorders including schizophrenia (Freedman et al, 1994(Freedman et al, , 1997, Alzheimer's disease (Nordberg et al, 1989(Nordberg et al, , 1990), Parkinson's disease (Janson et al, 1988;Reavill, 1990;Grandinetii et al, 1994), and Tourette's syndrome (Sandberg et al, 1988(Sandberg et al, , 1989. Currently available neuropsychiatric medications work primarily by inhibiting neurotransmission through postsynaptic receptor antagonism or by inhibiting neurotransmitter reuptake or catabolism (Schatzberg et al, 1995).…”
mentioning
confidence: 99%
“…A PET imaging study showed lower accumulation of 11 C-nicotine in the brains of Alzheimer disease patients than in age-matched healthy controls, implying the loss of nicotinic receptors in Alzheimer disease (28). PET studies on patients with Alzheimer disease were also effective in finding a direct correlation between 11 C-nicotine levels in the parietal cortex and the results of a clockdrawing test (16).…”
Section: Discussionmentioning
confidence: 88%